SIMULASI DAN SOSIALISASI MITIGASI BENCANA BAGI PENYANDANG DISABILITAS DI SEKOLAH LUAR BIASA ACEH TIMUR - Teuku Hasan Basri; Nuraini (Global Science Society, 2020)
Persons with disabilities meet unique challenges in each stage of disaster management, the only thing that is seen is physical disturbances, but what actually happens is physical, social, and economic disturbances. These problems must immediately get a solution because Indonesia has ratified the Convention on the Right of Person With Dsability (CRPD) through Law 19 of 2011. The goal is to provide alternative solutions for persons with disabilities in dealing with disasters that arise in the East Aceh region, Providing additional knowledge to persons with disabilities about the importance of facing disaster awareness that often occurs in the East Aceh region. Directly teach how simulation in the face of disasters that will occur in the East Aceh region for persons with disabilities and motivate the region of persons with disabilities to always be active and prepared to face disasters that will occur at any time. This Community Service Method has been conducted for 3 (three) months from May to July 2019. The service is carried out in the first way, socialization to students with disabilities in East Aceh district. The results of the dedication show that disaster mitigation socialization provides an alternative in understanding students with disabilities so that people can know how to deal with disasters such as floods, earthquakes and others that often occur in coastal areas. Students and teachers better understand how to deal with disaster mitigation and related first aid in the face of a disaster that occurs and how to deal with the alertness of disaster mitigation. The lack of knowledge of teachers and students in knowing how to deal with natural disasters and the limitations of communication tools in Special Schools East Aceh District is very lagging and in general students and teachers around do not have access to handling disaster mitigation in the Special District School of East Aceh.